Hair cortisol concentrations and cortisol stress reactivity in generalized anxiety disorder, major depression and their comorbidity. (January 2017) - Steudte-Schmiedgen, Susann; Wichmann, Susann; Stalder, Tobias; Hilbert, Kevin; Muehlhan, Markus; Lueken, Ulrike; Beesdo-Baum, Katja
Abstract: Studies investigating cortisol secretion in patients with generalized anxiety disorder (GAD) have reported heterogeneous findings. Further, current knowledge on the specificity of endocrine changes for GAD and/or comorbid major depression (MD) is limited. Hence, the current study investigated long-term integrated cortisol secretion, as indexed by hair cortisol concentrations (HCC), and experimentally-induced cortisol stress reactivity in relation to GAD, MD and their comorbidity. Carefully characterized groups of 17 GAD patients including 8 with comorbid MD (GAD-MD), 12 MD patients and 21 healthy controls were recruited. Alongside psychometric data, HCC ( N = 43) and salivary cortisol stress reactivity in response to the Trier Social Stress Test ( N = 45) were determined. Findings revealed that MD patients exhibited lower HCC compared to controls and GAD patients, with no differences between the latter two groups. Interestingly, when the GAD group was separated into two groups based on MD comorbidity, lower HCC in MD patients were found compared to controls and GAD-noMD patients, but did not show differences when compared to GAD-MD patients. No HCC differences were seen between GAD-MD or GAD-noMD patients and healthy controls. No TSST group differences emerged. Our findings suggest MD to be related to long-term attenuation in cortisol secretion. While no group differences emerged between patients with GAD, neither with nor without MD, and controls, the current results provide tentative evidence that MD determines long-term endocrine changes, with pure GAD showing a distinct pattern. Future studies are needed to confirm our findings in larger samples of pure and comorbid groups. Highlights: Cortisol in relation to GAD, MD and their comorbidity investigated. Two endocrine markers: hair cortisol and salivary cortisol stress reactivity. MD is related to long-term attenuation in cortisol secretion. No hair cortisol group differences between GAD patients and controls. Endocrine dysregulation in MD (with or without GAD), with pure GAD being distinct.